PENGOLAHAN AIR GAMBUT MENGGUNAKAN KOAGULAN CAIR DARI LEMPUNG ALAM CENGAR - Reza Syahroni; Muhdarina '; Amilia Linggawati (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Cengar clay is used as feedstock for the production of liquid coagulant. Liquid coagulant is used for improve peat water quality. Liquid coagulant was obtained by calcining clay at temperature 700 °C for 3 hours and leaching with 0.2 mol H 2 SO 4 . Variation of leaching conditions were selected at temperatures 30, 60, and 100 °C at 1, 2, and 3 hours. Then, liquid coagulant was used in peat water treatment processes with some parameters such as odor, color, pH, turbidity, TSS (Total Suspended Solid), TDS (Total Dissolved Solid), and dissolved organic acids. The results of peat water parameters after treatment were compared to PP No.82 of 2001 on Water Quality and Water Pollution Control and PERMENKES 416/ Health Minister/PER/IV/1990 about Drinking Water Quality. The results showed that almost all of liquid coagulants were capable to reduce of odor, turbidity, and TDS in peat water. However, one liquid coagulant type of K 100-2 can reduce peat water quality to be odorless, pH of 8,05, turbidity of 4 NTU, TDS of 278 mg/L, and TSS of 7 mg/L.